2016
DOI: 10.1002/mnfr.201600141
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to a Western‐style diet causes differences in intestinal microbiota composition and gene expression of suckling mouse pups

Abstract: ScopeThe long‐lasting consequences of nutritional programming during the early phase of life have become increasingly evident. The effects of maternal nutrition on the developing intestine are still underexplored.Methods and resultsIn this study, we observed (1) altered microbiota composition of the colonic luminal content, and (2) differential gene expression in the intestinal wall in 2‐week‐old mouse pups born from dams exposed to a Western‐style (WS) diet during the perinatal period. A sexually dimorphic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 62 publications
0
38
0
1
Order By: Relevance
“…Infants of obese and high gestational weight gain women demonstrate lower concentrations of the genus Bifidobacterium, considered protective bacteria, and higher concentrations of proinflammatory bacteria, including Bacterioides, Clostridium, and Staphylococcus [21]. Similarly, in rodents, consumption of a high-fat diet (HFD) or a Western diet prior to and during pregnancy could alter the trajectory of maternal and offspring microbiota [22]. Putative mechanisms of dysbiosis that could lead to obesity might be due to increased energy extraction and storage from ingested nutrients [23].…”
Section: Gut-brain Axismentioning
confidence: 99%
“…Infants of obese and high gestational weight gain women demonstrate lower concentrations of the genus Bifidobacterium, considered protective bacteria, and higher concentrations of proinflammatory bacteria, including Bacterioides, Clostridium, and Staphylococcus [21]. Similarly, in rodents, consumption of a high-fat diet (HFD) or a Western diet prior to and during pregnancy could alter the trajectory of maternal and offspring microbiota [22]. Putative mechanisms of dysbiosis that could lead to obesity might be due to increased energy extraction and storage from ingested nutrients [23].…”
Section: Gut-brain Axismentioning
confidence: 99%
“…; Steegenga et al . ). Pregnancy shifts the abundance and type of bacteria that colonize the maternal intestine (Koren et al .…”
Section: Introductionmentioning
confidence: 97%
“…The relationship between intestinal microbes and host metabolism has become one of most studied factors mediating obesity risk and maternal HFD has been linked to an altered offspring microbiota (Ma et al 2014;Chu et al 2016;Steegenga et al 2017). Pregnancy shifts the abundance and type of bacteria that colonize the maternal intestine (Koren et al 2012) and these shifts have been suggested to contribute to maternal metabolic adaptations and pregnancy outcomes (Koren et al 2012;Goltsman et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The priority effects important to human health has an origin from the ealy life according to ecological theory and circumstantial evidence [59][60][61]. The mechanisms, conditions and consequences of priority effects that might affect microorganisms in the gut, bacterial community remains highly conserved between corresponding body sites in human hosts, while gene transcription is much more variable [60].…”
Section: Hereditary Factors and Family Diet Historymentioning
confidence: 99%